Hector M. Patmore – Josef Lössl (eds.), Demons in Early Judaism and Christianity . Characters and Characteristics (Ancient Judaism and Early Christianity 113; Leiden – Boston, MA: Brill 2022) - Krzysztof Kinowski (The Biblical Annals, 2023)
Recenzja książki: